PENGARUH PERIODE BEBAS GULMA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN GANDUM (Triticum aestivum L.) Genotif 10 - Endi Irfani; Yohanes Hendro Agus (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2021)
Wheat in Indonesia is the second staple food. Wheat seed are processed to become wheat flour.From wheat flour can be made noodle, bread and other foods. One factor that is affected wheatproductivity is competition between wheat and weeds. The aim of the research were to know theaffect of weeding times toward growth and yield of wheat of Genotype 10, and to know weedingperiods that were critical periods of free weed of Genotype 10 wheat. This research usedRandomized Completely Block Design (RCBD) with eight treatments and five replications. Thetreatments tested were four periods of wheat crop without weeds and four periods of wheat cropwith weed. Research result data were analyzed by using analysis of variance (ANNOVA) andhonestly significant different (HSD) at 95% significant level. Research results showed that: (1)both periods with and without weeds affected number of tillers per clump, seed weight perpanicle, and (2) Seed weight per clump in period of weed controlled was highest significantlycompared with seed weight per clump in period with weed. It could be concluded that criticalweed- free periods of Genotype 10 of wheat were between 14 days until 42 days after sowing.